WORKER OF IDEA: RETURNING OF VASYL DOMANYTSKY (1877-1910) Vasyl Domanytsky. From the scientific-creative inheritance: Articles, essays, reviews. In two books. Book first. – Chercasy: publisher of Yu. Chabanenco, 2010. – 440 s.; Vasyl Domanytsky. From the - Sevrasevych, M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In a review the question is a few books devoted to the not popular figure in the Ukrainian culture to Vasyl Domanytsky (1877-1910).